CAEV Vif Hijacks ElonginB/C, CYPA and Cullin5 to Assemble the E3 Ubiquitin Ligase Complex Stepwise to Degrade oaA3Z2-Z3 - Zhao, Zhilei; Li, Zhaolong; Huan, Chen; Wang, Hong; Su, Xing; Zhang, Wenyan (Frontiers in Microbiology, 2019)
Caprine arthritis encephalitis virus (CAEV) is a lentivirus that causes multisystemic chronic disorders in sheep and goats. It encodes Vif to counteract the restriction of Ovis aries A3Z2-Z3 (oaA3Z2-Z3) by inducing their degradation. Nevertheless, the mechanisms underlying the interplay between CAEV Vif and OaA3Z2-Z3 have yet to be elucidated. Here, we identified the cellular factors ElonginB/C, CYPA and Cullin5 as being hijacked by CAEV Vif as well as several functional domains of CAEV Vif required for degrading oaA3Z2-Z3. Moreover, we determined that CAEV Vif assembled E3 ubiquitin ligase stepwise via its SLE motif (170SLE172) to recruit ElonginB/C, the P21 site and the zinc finger motif (C132-C134-C154-C157) to recruit CYPA, as well as the hydrophobic domain (141IR142) to recruit Cullin5. And this CAEV Vif-mediated E3 ligase triggers the proteasomal degradation of oaA3Z2-Z3, which directly bind CAEV Vif through residues Y39 and L44. In particular, CYPA played an essential role in the process to regulate ligase assembly, which was analogous to CBF-β, the essential regulator for HIV-1 and SIV-mediated E3 ligase, indicating that there is a modular conservation and lineage-specific preference for cellular partners required by Vifs from different subgroups of lentiviruses. Taken together, these findings provide important insights regarding the CAEV Vif function and deepen our understanding of the arms race between the lentiviruses and their hosts.